Lime, inoculum, and phosphorous input supplementation under rain-fed soybean in Ghana's northern savannas - Awuni, George A.; Reynolds, Daniel B.; Dodds, Darrin; Denwar, Nicholas N.; Abdulai, Alhassan L.; Asungre, Peter A.; Yahaya, Iddrisu; Goldsmith, Peter D. (Frontiers in Sustainable Food Systems, 2023)
Recent prices in soybean have spurred interest in motivating growers into input integration to improve yields across the northern savannas of Ghana. However, there needs to be more knowledge of soybean yield and profitability between low-input and high-input integration under abiotic weather stressors and low soil fertility. A 3-yr study investigated three inputs at two treatment levels (with or without) in low (1-way), medium (2-way), and high (3-way) input combinations for soybean yield, yield components, rain use efficiency, and economic profitability. The single-input application of lime (T1), inoculum (T2), and phosphorus (T4) are the low-input system. The medium input systems included lime × inoculum (T3), lime × phosphorus (T5), and (inoculum × phosphorus (T6), while the high input system was T7 (lime × inoculum × phosphorus), and a no-input treatment as the control. The soils were inherently low in fertility, and weather variability during the reproductive stages was a significant limiting factor to improving grain yield across locations. Grain yield was highest in 2017 at Manga and Nyankpala, and in 2019 at Wa. Except at Manga, grain yield and rain use efficiency (RUE) was highest in the high input system (T7). However, marginal net benefits (MNB) and marginal rate of returns (MRR) were highest in the low input system (T2) across locations. The low (T1) and medium (T3) input systems (except Nyankpala) were dominant for MNB and MRR due to the high cost of the product. These results suggest that smallholder farmers prefer low input (T2) with the least cost of production and the highest marginal net benefit and marginal rate of returns. Nevertheless, producers would have to evaluate their resource base and the cost of nutrient integration for sustainability. This paper recommends further studies on lime rates to determine profitability and the long-term (residual) effect of lime alone and synergic with inoculum or phosphorus.